Sites of Resistance: Justice, Healing, and Liberation in Octavia E. Butler's Fledgling. - Whiteside, Briana (Femspec, 2023)
A literary criticism by Briana Whiteside explores Octavia E. Butler's novel "Fledgling" as a resistance narrative, focusing on the use of the vampire figure to examine historical harm and silencing of Black women. Topics include the portrayal of the vampire as a vehicle to challenge societal dominance, the racial tensions and anxieties surrounding the protagonist's mixed-race identity, and the exploration of memory gaps and healing.